The reality of polarizing professional human resources in the Jordanian higher education institutions - Mohammad Omar Al-Momani; Mariam Ayed Murtada; Karimah Suleiman Aljedayah; Maaly Mefleh Al-Mzary; Lubna Mahmoud Obeidat; Elham Mahmoud Rababa (International Journal of Evaluation and Research in Education (IJERE), 2023)
The study aimed to identify the reality of polarizing professional human resources from the point of view of academics in Jordanian higher education institutions (JHEI), following the variables: gender, educational qualification, academic qualifications, years of service, and type of institution. The study followed a descriptive-analytical approach. The study sample comprised 674 faculty members working in various institutions of the JHEI. The researcher used a questionnaire comprising 24 items as a study instrument. The study’s findings revealed that the JHEI for polarizing professional human resources were ordinary. and that academic institution administrations encourage personnel to submit distinguished ideas. Also, they seek to adopt a philosophy of change as needed, while the administrations do not care about measuring the job satisfaction of employees. Periodically, it was found that JHEI encourage feedback from students to improve the quality of services and adopt modern technological means to provide their services.